2022
DOI: 10.1038/s41598-022-17635-9
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow between wild trees and cultivated varieties shapes the genetic structure of sweet chestnut (Castanea sativa Mill.) populations

Abstract: Gene flow between cultivated and wild gene pools is common in the contact zone between agricultural lands and natural habitats and can be used to study the development of adaptations and selection of novel varieties. This is likely the case in the northern Adriatic region, where centuries-old cultivated orchards of sweet chestnut (Castanea sativa Mill.) are planted within the natural distribution area of the species. Thus, we investigated the population structure of several orchards of sweet chestnuts. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 100 publications
(151 reference statements)
0
2
0
Order By: Relevance
“…The species was extensively cultivated in southern Europe for nuts and timber since the Roman Empire (Fernández‐López et al, 2021; Krebs et al, 2019; Marinoni et al, 2013; Mattioni et al, 2017). Recent studies revealed significant translocation of germplasm between the Iberian and Apennine peninsulas (Fernández‐López et al, 2021) and a considerable gene flow between cultivated orchards and natural populations in the Adriatic region (Tumpa et al, 2022). However, sweet chestnut is also found isolated in the Caucasus ecoregion, a global biodiversity hotspot (Tarkhnishvili et al, 2012; Zazanashvili et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The species was extensively cultivated in southern Europe for nuts and timber since the Roman Empire (Fernández‐López et al, 2021; Krebs et al, 2019; Marinoni et al, 2013; Mattioni et al, 2017). Recent studies revealed significant translocation of germplasm between the Iberian and Apennine peninsulas (Fernández‐López et al, 2021) and a considerable gene flow between cultivated orchards and natural populations in the Adriatic region (Tumpa et al, 2022). However, sweet chestnut is also found isolated in the Caucasus ecoregion, a global biodiversity hotspot (Tarkhnishvili et al, 2012; Zazanashvili et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the most used and reliable tool is focused on simple sequence repeats (SSRs), which are broadly adopted to also assess the genetic variability of many fruit species [32][33][34][35][36][37][38]. In this context, their application in C. sativa germplasm has already been developed, leading to the genetic characterization of several varieties in the whole of Europe [3,[39][40][41][42][43]. Specifically, SSR markers have been previously used to elucidate the relationships among European and Italian chestnut varieties [5,[44][45][46][47] and assess the genetic diversity of cultivars and accessions across Italy, spanning from the southern to northern regions [15,19,[48][49][50].…”
Section: Introductionmentioning
confidence: 99%